Ti Substitution in Li5FeO4: A Li-Rich Cathode Material for Li-Ion Batteries from First Principles Calculations. (14th October 2021) - Maria Augustine, Anu; Sudarsanan, Vishnu; Ravindran, P
Abstract : Li-rich materials with simultaneous anionic and cationic reductions are one among the most promising class of cathode materials for high−capacity Li-ion batteries. The recent studies on the Li-rich Li5 FeO4 with defect antifluorite-type structure show that Li5 FeO4 can generate high capacity by simultaneous reduction of Fe and O atoms without any obvious release of oxygen gas. But, the poor cyclability as well as electrical conductivity of Li5 FeO4 makes it a less attractive cathode for Li-ion batteries in practical applications. In the present study, we have substituted the Fe sites with Ti in different concentrations (Li5 Fe1− x Ti x O4 with x = 0.125, 0.250, 0.375, 0.500, 0.625, 0.750, 0.875, 1.00) and investigated the structural, electronic and Li-diffusion properties using density functional theory calculations. The total energy calculations show that all the Ti substituted systems have negative enthalpy of formation and this implies that the Ti substituted materials are also stable. The analysis of the calculated density of states indicates that Ti substitution reduces the bandgap and thereby improves the electronic conductivity of these materials. Similarly, the analysis of Li migration in Ti substituted Li5 FeO4 shows lower barrier height compared to that in the parent compound indicating the possibility of fast diffusion of Li-ions by Ti substitution.